2013
DOI: 10.1017/s0007114513002109
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption and nutritional and biochemical status of 0·5–12-year-old Indonesian children: the SEANUTS study

Abstract: Indonesia is currently facing the double burden of malnutrition. While undernutrition is still a major public health problem, the prevalence of overnutrition is increasing. The objective of the South East Asian Nutrition Survey (SEANUTS) was to provide up-to-date data on nutritional status, food consumption and biochemical parameters related to nutrition for children aged 0·5-12 years. The SEANUTS study in Indonesia was conducted in a nationwide representative sample of 7·211 children using multistage cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
5
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 11 publications
13
114
5
11
Order By: Relevance
“…The sampling procedures followed in each one of the four SEANUTS countries are described in detail elsewhere (17,(19)(20)(21)(22) . In brief, both Indonesia and Thailand used population-based sampling approaches, whereas Malaysia and Vietnam performed their sampling in nurseries, kindergartens and primary schools.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling procedures followed in each one of the four SEANUTS countries are described in detail elsewhere (17,(19)(20)(21)(22) . In brief, both Indonesia and Thailand used population-based sampling approaches, whereas Malaysia and Vietnam performed their sampling in nurseries, kindergartens and primary schools.…”
Section: Samplingmentioning
confidence: 99%
“…More information on the algorithm used for the power analysis and sample size calculation in the present study is provided elsewhere (17,(19)(20)(21)(22) .…”
Section: Power Analysismentioning
confidence: 99%
“…Dealing with short-latency deficiency diseases is in principle relatively straightforward, the main difficulties usually being establishing the deficiencies at the population level. Recent, nationally representative studies in Indonesia and Malaysia reported vitamin D deficiency (using the cutoff of 50 nmol/L; 20 ng/mL) in over 60% of girls 7-12 years old [17][18][19], which had never been measured before. Fortification has proven to be an effective way to increase intakes of selected nutrients in both developed and developing countries [9], although sub-optimal data is often found in estimating population deficiencies and food intakes of potentially fortified foods.…”
Section: "Conflicts" Of Evidencementioning
confidence: 99%
“…20 Perbedaan ini terjadi karena prevalensi anak yang kekurangan vitamin D di Indonesia lebih besar (44%) dibandingkan dengan di Mesir (15%). 21,22 Pada penelitian di India 23 (2013), rerata dari usia pasien anak dengan sepsis adalah 4,2 tahun dan median kadar calcifediol 19,7 ng/mL dengan prevalensi pasien sepsis yang mempunyai kadar calcifediol <20 ng/mL lebih tinggi (51%) dibandingkan dengan kontrol (17%). Penelitian di Mesir 20 (2015) menunjukkan rerata dari usia pasien anak dengan sepsis adalah 8 tahun dan rerata dari kadar calcifediol 24,5 ng/mL.…”
Section: Pembahasanunclassified